Bone Scan or 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography; Which Modality Better Shows Bone Metastases of Breast Cancer? - Balci, Tansel A.; Koc, Zehra P.; Komek, Halil (Karger, 2012)
Background: In this multicenter study, we aimed to compare concurrent F-18-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) and bone scan results of breast cancer patient. Patients and Methods: 162 patients with breast cancer (158 female, 4 male; mean age 50.6 years) were included in the study. FDG PET/CT examination was performed in all patients, and concurrent bone scintigraphy in 68 patients. The results of FDG PET/CT and bone scan were compared. Results: 132 of the 162 patients were operated on because of breast cancer. 89 patients had metastasis, and 4 had recurrent disease according to FDG PET/CT results. Metastatic sites in order of frequency were lymph nodes, bone, lung, liver, adrenal gland, local skin or muscle, brain, and peritoneum (peritonitis carcinomatosa). The sensitivity, specificity, accuracy, and negative and positive predictive value of bone scintigraphy versus FDG PET/CT were 96 vs. 100%, 100 vs. 98%, 100 vs. 83%, 100 vs. 100%, and 90 vs. 100%, respectively. Conclusion: Although the 2 modalities were in concordance with each other, in 5 (21%) cases, FDG PET/CT could not show bone metastasis which were detected on bone scintigraphy. Hence, bone scintigraphy was superior to FDG PET/CT in the determination of bone metastasis derived from breast cancer. However, FDG PET/CT should be considered for soft tissue metastasis.
Keywords: Breast cancer; Bone metastasis; FDG PET/CT; Bone scintigraphy